Environmental cues in different host niches shape the survival fitness of Staphylococcus aureus - JuOae Chang; ChaeYoung Lee; Inseo Kim; Jihyeon Kim; Ji-Hoon Kim; Taegwan Yun; David C. Hooper; Suzanne Walker; Wonsik Lee (Nature Communications)
Abstract The ability of Staphylococcus aureus to adapt and thrive in diverse host niches adds to the challenge in combating this ubiquitous pathogen. While extensive research has been pursued on the adaptive mechanisms of methicillin-resistant S. aureus (MRSA) in various infection models, a comprehensive analysis of its fitness across different host niches is lacking. In this study, we employ transposon sequencing to analyze the adaptive strategies of MRSA in various infection niches. Our analysis encompasses a cell model that mimics an intracellular niche, human blood, which represents a major extracellular environment as well as a major intermediary route encountered by bacteria during systemic infection, and a male murine sepsis model that recapitulates intra-organ environments. Our findings reveal substantial differences in the genetic determinants essential for bacterial survival in intracellular and blood environments. Moreover, we show that each organ imposes unique growth constraints, thus fostering heterogeneity within the mutant population that can enter and survive in each organ of the mouse. By comparing genes important for survival across all examined host environments, we identify 27 core genes that represent potential therapeutic targets for treating S. aureus infections. Additionally, our findings aid in understanding how bacteria adapt to diverse host environments.